ANALYZE OF THE PHYSICAL-CHEMICAL PROPERTIES OF THE SOIL IN THE AREA POSTA RAT / TURDA - SUR, Ioana Monica; TECSA, Ana-Maria; MICLE, Valer; GABOR, Timea (Studia Universitatis Babeș-Bolyai Ambientum, 2018)
The most important contaminated areas from Cluj County are the uncontrolled HCH scrap deposits from Turda city, which appeared as a result of the industrial activity of the former Chemical Plant Turda. Over the years, were identified 4 locations in the area. The four contaminated locations situated in the area of Turda city Sum up to 60000 tons of HCH polluted soil are. One of these zones is the Posta Rat area (40000 m2) which is situated on the left bank of Aries River. The objective of this paper is to carry out experimental researches in order to establish the physical-chemical properties of the soil from Posta Rat area, soil contaminated with HCH (hexachlorocyclohexane). The texture, structure, humidity and pH are the main analysis performed in order to determine the optimum cleaning technologies for the deteriorated soil as a result of the activity of the Chemical Plant in Turda. The results of the physical-chemical analysis can point out the most suitable cleaning soil solution, because as a result of the study, the characteristics of the soil are known, being much easier to identify the applicability limits of the cleaning solutions.